2021
DOI: 10.1126/sciadv.abj9537
|View full text |Cite
|
Sign up to set email alerts
|

Processive cleavage of substrate at individual proteolytic active sites of the Lon protease complex

Abstract: One-way translocation and processive cleavage of substrate polypeptide occur in each of the Lon proteolytic active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Rigid body fitting of three N-terminal homology domains indicated that the extended substrate protein contacted H391 and Y394 of a conserved HRKY linker helix motif. In bacterial LonPs from Thermus thermophilus (Coscia and Lowe, 2021) and Meiothermus taiwanesis (Li et al, 2021), the arrangement of the odd-numbered N domains is like in LonP1. In the absence of density in the scattering potential maps, even-numbered N domains of these bacterial LonPs were modeled under the assumption that their long linker a-helices would be straight.…”
Section: Overall Architecturementioning
confidence: 99%
“…Rigid body fitting of three N-terminal homology domains indicated that the extended substrate protein contacted H391 and Y394 of a conserved HRKY linker helix motif. In bacterial LonPs from Thermus thermophilus (Coscia and Lowe, 2021) and Meiothermus taiwanesis (Li et al, 2021), the arrangement of the odd-numbered N domains is like in LonP1. In the absence of density in the scattering potential maps, even-numbered N domains of these bacterial LonPs were modeled under the assumption that their long linker a-helices would be straight.…”
Section: Overall Architecturementioning
confidence: 99%
“…Furthermore, while experimental evidence is regarded as the ground truth when creating prediction models, the PDB has known issues such as redundancy 44 or enzyme-inhibitor complexes marked as enzyme-substrate complexes [45][46][47] . For serine endopeptidase La (EC: 3.4.21.53), none of the eight test PDBs are correctly predicted.…”
Section: Datasets Usedmentioning
confidence: 99%
“…For serine endopeptidase La (EC: 3.4.21.53), none of the eight test PDBs are correctly predicted. Notably, one is described to have no activity (4fwh), three are characterized in complex with inhibitors (4fw9, 4fwd, 4fwg), and the other four are from a mutation study where they mutated the catalytic dyad residues (7ev4, 7euy, 7ev6, 7eux) 46,47 . Yet, these structures are all marked as having enzymatic activity with EC classification 3.4.21.53 in the PDB.…”
Section: Datasets Usedmentioning
confidence: 99%
“…Finally, another omnipresent energy‐dissipating protease, LonA, uses ATP but also polyphosphate as its energy source (Ropelewska et al, 2020 ). It degrades protein substrates in a processive fashion (Li, Hsieh, et al, 2021 ). As stated previously, it uses SmiA as an adaptator for SwrA degradation (Hughes et al, 2018 ; Olney et al, 2022 ).…”
Section: The Proteostasis Networkmentioning
confidence: 99%